Liquid state bioconversion of domestic wastewater sludge for bioethanol production - Alam, Md. Zahangir; Kabbashi, Nassereldeen; Razak, A. A. (Springer Science, 2007)
The production of bioethanol was conducted by utilizing domestic wastewater sludge as major substrate using the yeast, Saccharomyces cerevisiae in liquid state bioconversion method (submerged fermentation). The optimum media and process conditions obtained from previous studies by using central composite design were applied in this study to evaluate the bioconversion process through ethanol production.The results presented in this study showed that 9.8% ethanol was produced utilizing sludge as substrate by Saccharomyces cerevisiae within 48 hours of fermentation while the COD, copper and chromium (heavy metals) removal were found to be 62%, 68% and 45% respectively in treated sludge after 72 hours of fermentation period. The total suspended solids (TSS) as biosolids (microbial growth) was observed to evaluate the microbial performance in bioconversion process.The observed yield and productivity were determined as well.